The role of tissue allergy to brown antigen in the diagnosis of the initial stage of generalized parodontitum - Антоненко, Марина Юріївна; Решетник, Людмила Леонідівна; Зелінська, Наталія Антонівна; Значкова, Олена Аркадіївна; Ревич, Валентин Олександрович (Actual Dentistry, 2019)
The purpose of this research was to study tissue sensitization to bone antigen as an indicator of changes in the alveolar outgrowth at the initial stage of the GP. Materials and methods. The research is based on the observation of 132 patients (67 women and 65 men) 19–35 years old with an initial stage of the GP (main group), chronic (72 persons) and exacerbated (60 people). The comparative group consisted of 71 patients 19–35 years old, with generalized chronic catarrhal gingivitis (GCCG) in the remission stage (29 people) and exacerbation (42 people). Control group was presented by 30 people without clinical signs of periodontal tissue diseases. Interpretation of clinical parameters was evaluated by subjective and objective evidence using periodontal indices of inflammation and hygiene (PMA, Loe-Silness bleeding index, GI, integral ARI hygiene index). The evaluation of tissue sensitization to bone antigen was determined in the inhibition reaction of leukocyte migration (IRLM). Results and discussion. As a result of the research, there was no significant difference in the indicative periodontal indices in the main and comparative groups in the chronic course of the disease - GP and generalized catarrhal gingivitis. In acute course of generalized periodontitis of initial degree, the manifested tissue sensitization to bone antigen was noted in 80.0±5.13 % (p < 0.01) of patients, which was significantly higher than in chronic cases. In 20 % of patients with GP of primary degree of sensitization to bone antigen was noted. Patients in the comparative group, both in the remission period and in the accelerated course of catarrhal gingivitis, as well as in the control group, tissue sensitization to bone antigen was not established. Conclusions. It is confirmed that periodontal indices can not be considered as indicative indicators that reflect the state of the periodontal complex generally, but only as a reflection the state of soft tissues of the periodontal disease. The established degree of tissue sensitization to bone antigen in the overwhelming majority of patients with GP directly depends on the nature of the course and can be considered as an indicative pathognomonic factor in the differential diagnosis of GP of primary degree and generalized chronic catarrhal gingivitis. Key words: generalized periodontitis, generalized catarrhal gingivitis, bone antigen, tissue sensitization